Thermal expansion and Debye temperature of Ti-Zr-Ni quasi-crystal - Malykhin, S.V.; Pugachov, A.T.; Chernokhvostenko, E.E. (Functional Materials, 2006)
Thermal expansion coefficient and Debye temperature of single-phase Ti₄₁.₅Zr₄₁.₅Ni₁₇ quasi-crystal have been determined from changes in the positions and intensities of X-ray deffraction lines within 80-300 K temperature range. The thermal expansion of the icosahedral crystal has been found to be isotropic. The average thermal expansion coefficient and Debye temperature have been determined to be alpha = 8*10⁻⁶ K⁻¹ and Od = 340 K.